Priorities for the reconstruction of religious buildings in the old city of Mosul using Expert Choice program - Hilal Hammo, Zaid; A. Al-Salam , Nadia (Journal of Planner and Development, 2023)
This paper attempts to shed light on the most influential factors in the importance of religious buildings were destroyed because of the recent war due to the control of terrorist gangs of ISIS over the city of Mosul, and to prioritize their reconstruction and their role in reviving the historical center of Mosul.The research’s problem emerged in the lack of knowledge about the identifying the most influential factors in the importance of religious buildings and utilizing them to prioritize their reconstruction. This study aims to analyze the factors influencing the importance of religious buildings using the Expert Choice software through the Analytic Hierarchy Process (AHP) to reach an analysis of their weights and propose priorities for reconstruction.The hypothesis is that the priorities for reconstruction depend on the most prominent factors influencing the importance of religious buildings, considering their impact on the population and urban context. To achieve this goal,a descriptive analytical methodology and historical approach were used, which involved collecting information and sources from desk research by analyzing historical records, books, and studies that addressed religious building sites and their significance, in order to obtain a set of indicators related to urban,religious, social, and economic aspects and their use as data in the program, where a set of results emerged,the most important of which is that reconstruction strengthens people's morale after periods of war, conflicts, and politics. The significant role of buildings in revitalizing the surrounding areas and cities is manifested through the return of residents either to their homes or periodically to revive some celebrations in these buildings or considering them as tourist destinations due to the multiple values possessed by these buildings (spiritual, historical, aesthetic, and cultural).